Activation of AMP-Activated Protein Kinase and Stimulation of Energy Metabolism by Acetic Acid in L6 Myotube Cells - Maruta, Hitomi; Yoshimura, Yukihiro; Araki, Aya; Kimoto, Masumi; Takahashi, Yoshitaka; Yamashita, Hiromi (PLOS ONE, 2016)
Previously, we found that orally administered acetic acid decreased lipogenesis in the liver and suppressed lipid accumulation in adipose tissue of Otsuka Long-Evans Tokushima Fatty rats, which exhibit hyperglycemic obesity with hyperinsulinemia and insulin resistance. Administered acetic acid led to increased phosphorylation of AMP-activated protein kinase (AMPK) in both liver and skeletal muscle cells, and increased transcripts of myoglobin and glucose transporter 4 (GLUT4) genes in skeletal muscle of the rats. It was suggested that acetic acid improved the lipid metabolism in skeletal muscles. In this study, we examined the activation of AMPK and the stimulation of GLUT4 and myoglobin expression by acetic acid in skeletal muscle cells to clarify the physiological function of acetic acid in skeletal muscle cells. Acetic acid added to culture medium was taken up rapidly by L6 cells, and AMPK was phosphorylated upon treatment with acetic acid. We observed increased gene and protein expression of GLUT4 and myoglobin. Uptake of glucose and fatty acids by L6 cells were increased, while triglyceride accumulation was lower in treated cells compared to untreated cells. Furthermore, treated cells also showed increased gene and protein expression of myocyte enhancer factor 2A (MEF2A), which is a well-known transcription factor involved in the expression of myoglobin and GLUT4 genes. These results indicate that acetic acid enhances glucose uptake and fatty acid metabolism through the activation of AMPK, and increases expression of GLUT4 and myoglobin.